2016
DOI: 10.1037/ort0000179
|View full text |Cite
|
Sign up to set email alerts
|

Provider lived experience and stigma.

Abstract: Despite professional values about advocacy for people managing mental health challenges, research on mental health providers indicates that this group expresses as much or more stigma than laypeople. This article reports on a continuing education needs assessment of 101 mental health providers, including evaluation of (a) knowledge about recovery-oriented care, (b) work engagement, (c) provider lived experience with mental health challenges, and (d) stigma, measured as disidentification. In this group of provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 30 publications
2
42
0
5
Order By: Relevance
“…Mental health professionals have been shown to be reluctant to disclose their mental health experiences to colleagues (Gras et al, 2015;Harris et al, 2016). The "culture of nondisclosure" characterized by one survey study of Veterans Health Administration (VHA) providers, described fear of discrimination on the part of providers if they disclosed lived experience (Harris et al, 2016).…”
Section: Mental Health Professionals With Lived Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Mental health professionals have been shown to be reluctant to disclose their mental health experiences to colleagues (Gras et al, 2015;Harris et al, 2016). The "culture of nondisclosure" characterized by one survey study of Veterans Health Administration (VHA) providers, described fear of discrimination on the part of providers if they disclosed lived experience (Harris et al, 2016).…”
Section: Mental Health Professionals With Lived Experiencementioning
confidence: 99%
“…Mental health professionals have been shown to be reluctant to disclose their mental health experiences to colleagues (Gras et al, 2015;Harris et al, 2016). The "culture of nondisclosure" characterized by one survey study of Veterans Health Administration (VHA) providers, described fear of discrimination on the part of providers if they disclosed lived experience (Harris et al, 2016). Another survey of 77 providers with lived experience in the VHA found 36% endorsed "be cautious about disclosure" when asked, and about a third of the sample reported that none of their colleagues were aware of their lived experience (Boyd, Zeiss, et al, 2016).…”
Section: Mental Health Professionals With Lived Experiencementioning
confidence: 99%
“…Within these types of stigma, MHPs may experience unique aspects that prevent or delay help-seeking behaviours [6,23]. Harris et al [23] suggest a culture of nondisclosure exists within the mental health profession, and that this non-disclosure works to increase stigma among MHPs.…”
Section: Stigma and Help-seekingmentioning
confidence: 99%
“…Within these types of stigma, MHPs may experience unique aspects that prevent or delay help-seeking behaviours [6,23]. Harris et al [23] suggest a culture of nondisclosure exists within the mental health profession, and that this non-disclosure works to increase stigma among MHPs. Registration requirements concerning professional impairment and mandatory reporting may contribute to this culture of non-disclosure within the professions [6,24].…”
Section: Stigma and Help-seekingmentioning
confidence: 99%
“…Some recipients of care prefer working with licensed mental health professionals due to the notion that such clinicians are more competent in providing care than practitioners with lived experience (known as professionalized peers). Due to lingering stigma, many mental health providers with lived experience choose not to self-disclose commonality (Harris et al, 2016). Clinicians with lived experience are often labeled as "unreliable, dangerous, vulnerable, unpredictable, and lack[ing in] the capacity to occupy esteemed roles such as educators" or contribute meaningfully in clinical and academic settings (Dorozenko et al, 2016, p. 906).…”
Section: Examining the Credibility Gap: "Power In The People" 18mentioning
confidence: 99%